2016
DOI: 10.1007/s10529-016-2247-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of glucose by syntrophic association between Geobacter and hydrogenotrophic methanogens in microbial fuel cell

Abstract: Reduction of H partial pressure by archaea is an efficient approach in improving power output in a glucose-fed MFC system using Geobacter sp. as an inoculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…On the other hand, oxidation of acetate results in the production of higher amount of CO 2 in the anodic chamber. 45 On the other hand, the concentration of oxygen in the cathodic chamber was observed to decrease as a result of increment in the current density (see Fig. 7b).…”
Section: Resultsmentioning
confidence: 89%
“…On the other hand, oxidation of acetate results in the production of higher amount of CO 2 in the anodic chamber. 45 On the other hand, the concentration of oxygen in the cathodic chamber was observed to decrease as a result of increment in the current density (see Fig. 7b).…”
Section: Resultsmentioning
confidence: 89%
“…2b), showing that CCE-MFCs generated significantly higher methane concentration suggesting prolific activities of archaea on the anodes. In our recent study, methane gas production was found to be directly proportional to methanogenic population and methanogens identified as electron scavengers (Oyiwona et al 2016). A positive correlation (r 2 = 0.95, p < 0.05) exists between the number of methanogens and the daily methane production (Ding et al 2012).…”
Section: Evaluation Of Methane Production In Mfcsmentioning
confidence: 86%
“…Various types of bio-energies have been extensively investigated as alternatives to fossil fuels (Ogbonna, 2013;. These include bioethanol (Ogbonna et al, 2001;, 2013Ogbonna andOkoli, 2010, 2013), biogas (Onwosi and Okereke, 2009;Okeh et al, 2014), microbial fuel cells (Oyiwona et al, 2016(Oyiwona et al, , 2018 and biodiesel . Biodiesel is a good alternative to fossil fuels and it has most of the required positive attributes of biofuel.…”
Section: Introductionmentioning
confidence: 99%